Correction: Sulforaphane protected the injury of human vascular endothelial cell induced by LPC through up-regulating endogenous antioxidants and phase II enzymes. Issue 8 (5th August 2015) - Li, Baolong; Tian, Sicong; Liu, Xu; He, Canxia; Ding, Zhongqing; Shan, Yujuan
<x xml:space="preserve">Abstract</x> Correction for 'Sulforaphane protected the injury of human vascular endothelial cell induced by LPC through up-regulating endogenous antioxidants and phase II enzymes' by Baolong Li et al., Food Funct., 2015, DOI: 10.1039/c5fo00438a.